Improvement Extensive Reading Interest Primary School Pupils Bone-Bilingual Book Covid-19 Pandemic: It is a case study at Cikarang Selatan - Ainayya Azzahra; Alya Rahayu Gunardi; Arsal Maulana Nugeraha; Muhammad Kemal Jatnika Almuharam; M. Taufik Hidayat; Muhammad Yazidus Syukri; Sylva Aulia (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The primary objective of this study is to achieved reading interest in primary school pupils ranged between 7 up to 13 years old at South Cikarang, Indonesia. This research is conducted as a community services program at Ciantra village the local RT/RW (hamlet) 24th /10 local regency sub-district on South Cikarang region. The research method used in this study by using extensive reading for children entitled Bone bilingual book used audio-visual learning through mentoring program, The preliminary and post-researches were conducted as a qualitative descriptive approach with a case study to reveal some benefits of this extensive reading program from 10 children as population and samples. The data collection method used is interview and questionnaire. The research finding as follows; 1) the partners were highly interested in reading Bone book, 2) easy to access the audios and visuals, and 3) very useful for mentoring activities. The reading habit and interest are also shown in this program. Finally, further research and study can be done in similar program to investigate next level of extensive reading through various teaching methodologies.